THE IMPACT OF REAL EXCHANGE RATE ON TRADE BALANCE - Widarjono, Agus (Journal of Indonesian Economy and Business, 2005)
The purpose of this study is to investigate the relationship between the trade balanceand the real exchange rate for bilateral trade in merchandise goods between Indonesia and the US, Japan and Singapore as its major trading partner. This article employs theelasticity approach to analyze such a relationship. Johansen multivariate cointegration isproposed to examine the impact of depreciation of real exchange rate on trade balance. Totests for J-curve, a generalize impulse response function generated from a vector error-correction model is applied.Quarterly data over the period 1988:1-2003:4 are used for the analysis. Our findingsdemonstrate that the real exchange rate has a positive impact on the bilateral tradebalance between Indonesia and Japan and Singapore. The generalized Marshall-Lernercondition, however, seems to hold only for the bilateral trade balance between Indonesiaand Japan. This study also finds that there is an evidence for J-curve for Indonesiaâsbilateral trade balance with the Japan.Keyword: real exchange rate, trade balance, Marshal-Lerner Condition and J-curve